2017
DOI: 10.1080/14740338.2017.1361401
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes drugs and the incidence of solid cancers: a survey of the current evidence

Abstract: The evaluation of the relationship between the use of antidiabetic drug and the occurrence of cancer is extremely challenging, both from the clinical and pharmacoepidemiological standpoint. This narrative review described the current evidence supporting a relationship between the use of antidiabetic drugs and the incidence of solid cancers. Areas covered: Data from pharmacoepidemiological studies on cancer incidence were presented for the main antidiabetic drugs and drug classes, including human insulin and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 203 publications
0
5
0
Order By: Relevance
“…Chemotherapy-induced neuropathy is a significant source of morbidity in cancer patients, with high incidences (Table 1) and can be a doselimiting side effect for many classes of chemotherapy drugs [5]. Diabetes mellitus is a commonly encountered comorbidity among patients with solid tumors [6][7][8]. Diabetes mellitus and its accompanying metabolic syndrome have been shown to correlate with the development and outcomes of a number of solid tumors [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy-induced neuropathy is a significant source of morbidity in cancer patients, with high incidences (Table 1) and can be a doselimiting side effect for many classes of chemotherapy drugs [5]. Diabetes mellitus is a commonly encountered comorbidity among patients with solid tumors [6][7][8]. Diabetes mellitus and its accompanying metabolic syndrome have been shown to correlate with the development and outcomes of a number of solid tumors [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Series of cohort studies suggested that the use of sulfonylurea may increase, decrease, or have no effect on the risk of cancer when compared with other GLDs or non-user of sulfonylurea (28)(29)(30). However, most of these observational studies may have flaws in study design and data analysis methods (7,13). According to the systematic review conducted by Farmer (13), observational studies on comparing cancer risk between users of metformin and sulfonylurea varied in design, and the majority had risks of several kinds of bias due to time-varying confounding and other sources.…”
Section: Discussionmentioning
confidence: 99%
“…In China and some developed countries, the use of sulfonylureas is second only to or even exceeds the first-line oral GLD metformin ( 5 , 6 ). Although a large number of observational studies about the association between GLDs and cancer incidence have been conducted, evidence of the association between sulfonylurea and cancer risk is still highly controversial ( 4 , 7 ). Besides the diversity of study populations, the majority of these studies suffered from severe methodological limitations, such as immortal time bias and time-varying confounding, which have contributed to the current inconsistent findings ( 4 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, controlling postprandial hyperglycemia is an important target to prevent diabetes as well as diabetic complications. In clinical medicine, α-glucosidase inhibitors such as acarbose, miglitol, and voglibose, belong to the class of antidiabetic drugs used for improving postprandial hyperglycemia [8,9,10,11]. Currently, natural products and their derivatives constitute more than half of the drugs in the clinic [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%